(3LRA ef OjhGf GdUaj GdMdjs - (3GdSfHSj GdWGFj GdMdj, Uaj GdOjf, YHO GdYRjR Hf SQGjG Hf Ydj Hf CHj GdbGSe, (B750 (3g`s
(3ChdgG (B:s
(3GdHJ dG CdbGc EdG eGOMG (B*** (3CgOi Edjc ef GdbQjV GdeMceGs
(3BNQgG (B:s
(3eG Mf QYO heG YfJ eWhbI (B*** (3heG JYfJ MeGeGJ GdMeG WQHGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 18s
(3eYLe GdeDdajf(B: 2 / 160s
(3cTa GdXfhf(B: 2 / 797s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdCOHs